Ответ:
1)
[tex]8.4 + 1.75m[/tex]
2)
[tex]3x - 7[/tex]
3)
[tex]3y - a - b[/tex]
4)
[tex]254c + 48[/tex]
Объяснение:
[tex]15 \frac{1}{3} - 5 \frac{1}{3} (1 \frac{1}{3} - 1.5m) - \\ - 6.2m = \\ = \frac{46}{3} - \frac{16}{3} ( \frac{4}{3} - 15m) - 6.2m = \\ = 15.3 - 5.3(1.3 - 1.5m) - 6.2m = \\ = 15.3 - 6.9 + 7.95 - 6.2m = \\ = 8.4 + 1.75m[/tex]
[tex]x - (x - (3x - 7)) = \\ = x - (x - 3x + 7) = \\ = x - x + 3x - 7 = \\ = 3x - 7[/tex]
[tex]5y - (2y - ((2a - b) - \\ - 3a)) = \\ = 5y - (2y - (2a - b - 3a)) = \\ = 5y - (2y - 2a + b + 3a) = \\ = 5y - 2y + 2a - b - 3a = \\ = 3y - a - b[/tex]
[tex]2((64c + 20) - ( - 4 - \\ - 63c)) = \\ = 2(64c + 20 + 4 + 63c) = \\ = 128c + 40 + 8 + 126c = \\ = 254c + 48[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Дай пожалуйста лучший ответ, здесь всё идеально правильноОтвет:
1)
[tex]8.4 + 1.75m[/tex]
2)
[tex]3x - 7[/tex]
3)
[tex]3y - a - b[/tex]
4)
[tex]254c + 48[/tex]
Объяснение:
1)
[tex]15 \frac{1}{3} - 5 \frac{1}{3} (1 \frac{1}{3} - 1.5m) - \\ - 6.2m = \\ = \frac{46}{3} - \frac{16}{3} ( \frac{4}{3} - 15m) - 6.2m = \\ = 15.3 - 5.3(1.3 - 1.5m) - 6.2m = \\ = 15.3 - 6.9 + 7.95 - 6.2m = \\ = 8.4 + 1.75m[/tex]
2)
[tex]x - (x - (3x - 7)) = \\ = x - (x - 3x + 7) = \\ = x - x + 3x - 7 = \\ = 3x - 7[/tex]
3)
[tex]5y - (2y - ((2a - b) - \\ - 3a)) = \\ = 5y - (2y - (2a - b - 3a)) = \\ = 5y - (2y - 2a + b + 3a) = \\ = 5y - 2y + 2a - b - 3a = \\ = 3y - a - b[/tex]
4)
[tex]2((64c + 20) - ( - 4 - \\ - 63c)) = \\ = 2(64c + 20 + 4 + 63c) = \\ = 128c + 40 + 8 + 126c = \\ = 254c + 48[/tex]